Supporting the Systematic Assessment of Clinical Processes: the MedFlow Method - Saboor, S.; Chimiak-Opoka, J.; Ammenwerth, E. (Methods of Information in Medicine, 2007)
Objectives: Healthcare is characterized by complex cooperation between highly specialized healthcare departments. This often leads to inefficient clinical processes. In orderto improve these processes, a systematic assessment method is needed. Such methods are still missing. The objective of this paper is to propose and evaluate a method to support the systematic and semi-automatic assessment of clinical processes, with special focus on the quality of information logistics.Methods: Criteria for the quality of information logistics were collected based on literature research and system analysis. Appropriate quality checks for these criteria were developed. An extended process modelling notation was developed. The method was evaluated in a pilot study.Results: An own model integrates four sub-models with each concentrating on distinct process aspects (i.e., control flow, data flow, tool usage, organizational information). In orderto assess the quality of a process, selected process details are combined in “views”. Weak points are then detected by applying specific rule-sets on these views. Each rule-set represents a pattern of critical cross-points which are searched for in the appropriate view-matrix. The MedFlow method was evaluated in a first pilot study in radiological departments – applying quality checks for the detection of e.g. media cracks or testing the transcription of information objects.Conclusion: The MedFlow method is best used to assess clinical processes regarding their control flow and information handling. The latter directly influences the quality of communication and thusthe quality of whole processes. However, this must be evaluated in further studies.
Keywords: Process assessment (healthcare); process measure; health informatics; information system